A Clinical Perspective on Advanced Developments in Bone Biopsy Assessment in Rare Bone Disorders - Treurniet, Sanne; Eekhoff, Elisabeth M. W.; Schmidt, Felix N.; Micha, Dimitra; Busse, Björn; Bravenboer, Nathalie (Frontiers in Endocrinology, 2020)
Introduction Bone biopsies have been obtained for many centuries and are one of the oldest known medical procedures in history. Despite the introduction of new noninvasive radiographic imaging techniques and genetic analyses, bone biopsies are still valuable in the diagnosis of bone diseases. Advanced techniques for the assessment of bone quality in bone biopsies, which have emerged during the last decades, allows in-depth tissue analyses beyond structural changes visible in bone histology. In this review we give an overview of the application and advantages of the advanced techniques for the analysis of bone biopsies in the clinical setting of various rare metabolic bone diseases. Method A systematic literature search on rare metabolic bone diseases and analyzing techniques of bone biopsies was performed in PubMed up to 2019 week 34. Results Advanced techniques for the analysis of bone biopsies were described for rare metabolic bone disorders including Paget’s disease of bone, osteogenesis imperfecta, fibrous dysplasia, Fibrodysplasia ossificans progressiva, PLS3 X-linked osteoporosis, Loeys-Diets syndrome, osteopetrosis, Erdheim-Chester disease and Cherubism. A variety of advanced available analytical techniques were identified that may help to provide additional detail on cellular, structural and compositional characteristics in rare bone diseases complementing classical histopathology. Discussion To date, these techniques have only been used in research and not in daily clinical practice. Clinical application of bone quality assessment techniques depends upon several aspects such as availability of the technique in hospitals, the existence of reference data and a cooperative network of researchers and clinicians. The evaluation of rare metabolic bone disorders requires a repertoire of different methods, owing to their distinct bone tissue characteristics. The broader use of bone material obtained from biopsies could provide much more information about pathophysiology or treatment options and establish bone biopsies as a valuable tool in rare metabolic bone diseases.